High Internal Phase Pickering Emulsion Stabilized by Lipase-Coated ZIF-8 Nanoparticles towards Recyclable Biphasic Biocatalyst - Chuanbang Xu; Yan Sun; Yuanyuan Sun; Ruiyun Cai; Shengmiao Zhang (Catalysts, 2023)
High internal phase Pickering emulsion (Pickering HIPE) stabilized by enzyme-decorated metal-organic frameworks (MOFs) nanoparticles is developed for biphasic biocatalysts to enhance lipase catalysis and recycling. Specifically, enzyme decorated nanoparticles are prepared via ZIF-8 physisorption of a model lipase Candida antarctica Lipase B (CALB), named ZIF-8@CALB, to be both Pickering stabilizer and catalytic sites. An oil-in-water (o/w) Pickering HIPE with oil/water volume ratio of 3 could then be fabricated by homogenizing p-nitrophenyl palmitate (p-NPP) n-heptane solution into the ZIF-8@CALB aqueous dispersion. The biocatalytic hydrolysis of p-NPP is conducted by just standing the biphasic system at room temperature. The Pickering HIPE system achieves a product conversion of up to 48.9% within 0.5 h, whereas the p-NPP n-heptane solution system containing free CALB only achieves a stable product conversion of 6.8% for the same time. Moreover, the ZIF@CALB could be recovered by a simple centrifugation at 800 rpm, and then reused in the next cycle. The hydrolysis equilibrium conversion rate of p-NPP keeps over 40% for all 8 cycles, reflecting the high catalytic efficiency and recyclability of the Pickering HIPE. This study provides a new opportunity in designing Enzyme-MOFs-based Pickering interfacial biocatalyst for practical applications.